2012
DOI: 10.1021/jp306333c
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interaction of Methylene Blue with Carbon Nanotubes: Theoretical and Mass Spectrometry Characterization

Abstract: Noncovalent interaction of methylene blue dye cation (MB + ) with single walled carbon nanotubes (CNT) is characterized by molecular dynamics (MD) simulation, quantum chemical calculations, and laser desorption/ionization (LDI) mass spectrometry. The MD simulation of the (MB + ) n −CNT (n = 1−10) complexes in water demonstrates that the MB + cations are adsorbed on the nanotube surface in the monomeric form. MD reveals both parallel and perpendicular orientations of the MB + tricyclic plane in relation to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 44 publications
5
42
0
2
Order By: Relevance
“…Close packing of the DOX/ PF/EB molecules on the surface was achieved when the longitudinal axes of the ligand and SWCNT were parallel, whereas for MB, they were perpendicular (a consequence of the MB chromophore being bent along the N-S atoms so that the shape mimics the curvature of the surface of SWCNT). The obtained structure of the MB-SWCNT complex is similar to that reported (Chagovets et al 2012). In addition, MD simulation was employed to verify the stability of such complexes by means of controlling the stability of geometry of the complex during the course of system evolution.…”
Section: Uv/vis Studysupporting
confidence: 87%
See 4 more Smart Citations
“…Close packing of the DOX/ PF/EB molecules on the surface was achieved when the longitudinal axes of the ligand and SWCNT were parallel, whereas for MB, they were perpendicular (a consequence of the MB chromophore being bent along the N-S atoms so that the shape mimics the curvature of the surface of SWCNT). The obtained structure of the MB-SWCNT complex is similar to that reported (Chagovets et al 2012). In addition, MD simulation was employed to verify the stability of such complexes by means of controlling the stability of geometry of the complex during the course of system evolution.…”
Section: Uv/vis Studysupporting
confidence: 87%
“…The hypochromic effect seen in the titration curves, as well as literature data (Chagovets et al 2012;Cheng and Adronov 2006;Gupta et al 2013;Ji et al 2009;Koh et al 2012;Nakashima 2006;Pan and Xing 2008;Rajendra et al 2004), also support the view that the main mode of ligand binding is stacking on the surface of SWCNT. It is suggested that the minimum site for ligand binding is a portion of SWCNT surface containing n carbon atoms.…”
Section: Uv/vis Studysupporting
confidence: 82%
See 3 more Smart Citations